Activated carbon adsorption material as well as preparation method and application thereof
By using a composite modified liquid to treat activated carbon raw materials, it is rich in nitrogen-containing high-active organic small molecules, and the Mannich reaction is used to decompose formaldehyde, solving the problems of limited adsorption capacity and secondary pollution of existing activated carbon materials, and achieving efficient and long-lasting formaldehyde adsorption and purification effects.
Patent Information
- Application Number
- CN202510064233.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-11
AI Technical Summary
The existing activated carbon materials have limited adsorption capacity for formaldehyde, their adsorption effect is not long-lasting, and there is a risk of secondary pollution.
By mixing the inorganic salt solution, organic amine solution and hydrophobic agent to form a composite modified solution, the activated carbon raw material is processed, which is rich in nitrogen-containing high-active organic small molecules, and the formaldehyde is decomposed by Mannich reaction to achieve efficient adsorption and purification.
It achieves efficient, long-lasting adsorption and purification of formaldehyde, avoids secondary pollution, and has significantly better effect than unchemically treated activated carbon.
Smart Images

Figure BDA0005243764900000111 
Figure BDA0005243764900000121
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of activated carbon modification, and in particular to an activated carbon adsorption material and a preparation method and application thereof. Background Art
[0002] Formaldehyde, as an important volatile organic compound (VOCs), is widely present in indoor and outdoor environments and has a significant impact on human health and atmospheric environmental quality. Due to its high reactivity, aldehydes play an important role in atmospheric chemical processes, affecting ozone generation and the formation of secondary organic aerosols. At the same time, formaldehyde is also one of the main pollutants in indoor air pollution. Long-term exposure to high concentrations of formaldehyde increases the risk of cardiovascular and respiratory diseases.
[0003] The field of air purification, especially formaldehyde purification technology, has always been the focus of environmental health research. With the improvement of people's living environment and the increase of health awareness, the market of formaldehyde-removing air purifiers continues to develop and technology continues to innovate.
[0004] At present, the existing technologies for purifying formaldehyde in the air mainly include chemical modification methods, which use oxidants such as HNO3, H2O2 or KMnO4 to treat activated carbon. The use of oxidants for modification is simple and can increase its surface functional groups, thereby improving its formaldehyde adsorption capacity.
[0005] Although the above chemical modification will allow activated carbon to carry certain groups that are conducive to the adsorption of formaldehyde molecules, in actual use, the formaldehyde purification effect is not good. When using oxidants such as H2O2 and KMnO4, the pH value change of the solution has an uneven oxidation effect on the activated carbon, and the increase in the concentration of HNO3 and KMnO4 solutions may be detrimental to the modification process. Oxidative modification changes the internal pore structure of activated carbon, but there is still an adsorption saturation problem. After changes in ambient temperature, humidity and pH, the internally adsorbed formaldehyde has the risk of escaping and causing secondary pollution.
[0006] The activated carbon materials in the prior art have limited adsorption capacity for formaldehyde and the adsorption effect is not long-lasting.
[0007] In view of this, the present invention is proposed. Summary of the invention
[0008] One object of the present invention is to provide a method for preparing an activated carbon adsorption material to solve the technical problem that the activated carbon material in the prior art has limited adsorption capacity for formaldehyde and the adsorption effect is not persistent. The method for preparing the activated carbon adsorption material of the present invention, through the coordination of various steps, obtains an activated carbon adsorption material that can efficiently and persistently adsorb formaldehyde and avoid secondary pollution.
[0009] Another object of the present invention is to provide an activated carbon adsorption material, which, in addition to its own abundant pores to adsorb formaldehyde, utilizes the highly active organic small molecules it carries to decompose formaldehyde, which can effectively adsorb and efficiently purify formaldehyde, and the chemical reaction of removing formaldehyde is irreversible, without secondary pollution, and the effect is long-lasting.
[0010] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0011] A method for preparing an activated carbon adsorption material comprises the following steps:
[0012] The inorganic salt solution, the organic amine solution and the hydrophobic agent are mixed to obtain a composite modified solution.
[0013] The activated carbon raw material is mixed with the composite modified liquid, the solid and liquid are separated, and the solid is collected and dried.
[0014] In some implementations, the mass fraction of the inorganic salt solution is 0.1% to 20%.
[0015] In some embodiments, in the inorganic salt solution, the inorganic salt comprises at least one of potassium chloride, sodium chloride, potassium sulfate, sodium bisulfate, sodium carbonate and potassium bicarbonate.
[0016] In some implementations, the mass fraction of the organic amine solution is 0.05% to 5%.
[0017] In some embodiments, the organic amine includes at least one of polyethyleneimine, 3-amino-1-propanol, 2,6-diaminocaproic acid, anionic polyacrylamide, cationic polyacrylamide and nonionic polyacrylamide.
[0018] In some implementations, the volume ratio of the inorganic salt solution to the organic amine solution is 1:(0.2-1).
[0019] In some embodiments, the hydrophobic agent includes at least one of methylvinyl silicone resin, vinyltriethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane and a silane coupling agent.
[0020] In some implementations, the mass fraction of the hydrophobic agent in the composite modified liquid is 0.1% to 2%.
[0021] In some embodiments, the inorganic salt solution, the organic amine solution and the hydrophobic agent are mixed, specifically comprising: dropping the hydrophobic agent into the mixture of the inorganic salt solution and the organic amine solution;
[0022] In some implementations, the mass ratio of the activated carbon raw material to the composite modified liquid is 1:(2-6).
[0023] In some embodiments, the activated carbon raw material includes at least one of coal-based activated carbon, coconut shell activated carbon and wood activated carbon.
[0024] In some embodiments, the mixing treatment includes ultrasonic treatment and immersion treatment.
[0025] In some embodiments, the ultrasonic treatment time is 2 to 15 minutes.
[0026] In some embodiments, the immersion treatment lasts for 1 to 8 hours, with stirring for 2 to 4 hours every 20 to 30 minutes.
[0027] In some embodiments, the drying temperature is 90 to 150° C., and the drying time is 2 to 12 hours.
[0028] An activated carbon adsorption material is prepared by the activated carbon adsorption material preparation method.
[0029] The application of the activated carbon adsorption material as described above in formaldehyde purification.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The method of the present invention uses a composite modified liquid to treat the activated carbon raw material, so that the activated carbon raw material is rich in nitrogen-containing highly active organic small molecules, which react with formaldehyde molecules to undergo a Mannich reaction. In addition to the ability of the activated carbon itself to adsorb formaldehyde through its abundant pores, the highly active organic small molecules are used to decompose formaldehyde, achieving effective adsorption and efficient purification. The chemical reaction for removing formaldehyde is irreversible, has no secondary pollution, and has a long-lasting effect.
[0032] (2) The activated carbon adsorption material of the present invention has excellent adsorption performance for formaldehyde. In addition to the performance of the activated carbon's own abundant pores to adsorb formaldehyde, it can utilize highly active organic small molecules to decompose formaldehyde, achieve efficient purification, and no secondary pollution. The effect is significantly better than that of unchemically treated activated carbon, and it can achieve strong purification of toxic and harmful formaldehyde, and has broad application prospects. DETAILED DESCRIPTION
[0033] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0034] According to one aspect of the present invention, the present invention relates to a method for preparing an activated carbon adsorption material, comprising the following steps:
[0035] Mix the inorganic salt solution, organic amine solution and hydrophobic agent to obtain a composite modified liquid. The inorganic salt plays a role in regulating pH and ion conduction. The small molecules of organic amine are important active components. On top of the performance of activated carbon's own rich pores to adsorb formaldehyde, they react with formaldehyde molecules to produce Mannich Reaction, effectively purifying and efficiently decomposing. The hydrophobic agent can reduce the competitive adsorption of polar water molecules in the air on the active sites, thereby improving the efficiency of adsorption purification.
[0036] The activated carbon raw material is mixed with the composite modified liquid, the solid and liquid are separated, and the solid is collected and dried.
[0037] The method of the present invention uses a composite modified liquid to treat an activated carbon raw material, so that the activated carbon raw material is rich in nitrogen-containing highly active organic small molecules, which react with formaldehyde molecules to undergo a Mannich reaction. Based on the performance of the activated carbon itself in adsorbing formaldehyde through its abundant pores, highly active organic small molecules are used to decompose formaldehyde, achieving effective adsorption and efficient purification. The chemical reaction for removing formaldehyde is irreversible, has no secondary pollution, and has a lasting effect.
[0038] In some embodiments, the mass fraction of the inorganic salt solution is 0.1% to 20%, including but not limited to 0.1%, 0.5%, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 20%, etc., or any range between the two. In some embodiments, in the inorganic salt solution, the inorganic salt comprises at least one of potassium chloride, sodium chloride, potassium sulfate, sodium bisulfate, sodium carbonate and potassium bicarbonate, such as a combination of sodium chloride and potassium sulfate, a combination of potassium sulfate and sodium bisulfate, a combination of sodium bisulfate, sodium carbonate and potassium bicarbonate, etc. The purity of the inorganic salt is greater than 98%.
[0039] In some embodiments, the mass fraction of the organic amine solution is 0.05% to 5%, including but not limited to 0.05%, 0.08%, 1%, 1.5%, 2%, 3%, 3.5%, 4%, 5%, etc., or any range between the two. In some embodiments, the organic amine includes at least one of polyethyleneimine, 3-amino-1-propanol, 2,6-diaminocaproic acid, anionic polyacrylamide, cationic polyacrylamide and non-ionic polyacrylamide, such as a combination of polyethyleneimine and 3-amino-1-propanol, a combination of 2,6-diaminocaproic acid, anionic polyacrylamide and cationic polyacrylamide, etc. The purity of the organic amine is greater than 95%.
[0040] In some embodiments, the volume ratio of the inorganic salt solution to the organic amine solution is 1:(0.2-1), such as 1:0.2, 1:0.3, 1:0.5, 1:0.8 or 1:1, etc. The inorganic salt solution and the organic amine solution are more conducive to synergistic effect when the volume ratio is appropriate.
[0041] In some embodiments, the hydrophobic agent includes at least one of methyl vinyl silicone resin, vinyl triethoxysilane, dodecyl trimethoxysilane, hexadecyl trimethoxysilane and a silane coupling agent, such as a combination of methyl vinyl silicone resin and vinyl triethoxysilane, a combination of dodecyl trimethoxysilane and hexadecyl trimethoxysilane, etc. In some embodiments, the mass fraction of the hydrophobic agent in the composite modified liquid is 0.1% to 2%, such as 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, etc., or any range between the two. The present invention adopts a suitable amount of hydrophobic agent, coordinated with other components, which is more conducive to modifying the activated carbon raw material so that it has a more excellent formaldehyde adsorption performance.
[0042] In some embodiments, the hydrophobic agent is added dropwise to a mixture of the inorganic salt solution and the organic amine solution.
[0043] In some embodiments, the inorganic salt solution and the organic amine solution are prepared by using water, such as deionized water. The inorganic salt solution, the organic amine solution and the composite modified solution are prepared by stirring at room temperature or by ultrasonication for 5 to 15 minutes to promote complete dissolution.
[0044] In some embodiments, the mass ratio of the activated carbon raw material to the composite modified liquid is 1:(2-6), such as 1:2.5, 1:3, 1:3.5, 1:4, etc. The activated carbon raw material and the composite modified liquid of the present invention adopt a suitable mass ratio, which is more conducive to modifying the activated carbon raw material so that it has excellent formaldehyde adsorption performance.
[0045] In some embodiments, the activated carbon raw material includes one or more of coal-based activated carbon, coconut shell activated carbon and wood activated carbon. The activated carbon raw material is pre-dried at 150° C. for 2 to 4 hours.
[0046] In some embodiments, the mixing treatment includes ultrasonic treatment and impregnation treatment. The mixed material is oscillated using an ultrasonic instrument, and the propagation of ultrasonic waves in the solution and the cavitation effect can better enable the modifier molecules in the composite modified liquid to enter the activated carbon pores. The ultrasonic treatment time is 2 to 15 minutes; after the ultrasonic treatment, the activated carbon material is removed, and then the impregnation treatment is performed. The impregnation treatment time is 1 to 8 hours, such as 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours or 8 hours, etc., and stirred for 2 to 4 hours (flowing for 2 hours, 3 hours or 4 hours, etc.) every 20 to 30 minutes (such as 20 minutes, 25 minutes or 30 minutes). Through sufficient impregnation treatment, it is more conducive to loading the modifier molecules and improving the adsorption performance of activated carbon for formaldehyde.
[0047] In some embodiments, the drying temperature is 90 to 150° C., such as 90° C., 100° C., 110° C., 120° C., 130° C., 140° C., 150° C., etc., and the drying time is 2 to 12 hours, such as 2 hours, 3 hours, 5 hours, 8 hours, 10 hours or 12 hours, etc. In some embodiments, the wet activated carbon is evenly spread on a sieve and placed in a blast drying oven with a pre-set temperature, the oven temperature is set to 90 to 150° C., and the drying is performed for 2 to 12 hours.
[0048] In some embodiments, the dried activated carbon adsorption material is naturally cooled to room temperature and sealed for storage.
[0049] According to another aspect of the present invention, the present invention also relates to an activated carbon adsorption material, which is prepared by the above-mentioned method for preparing the activated carbon adsorption material.
[0050] The activated carbon adsorption material of the present invention has excellent adsorption performance for formaldehyde. On top of the performance of the activated carbon itself in adsorbing formaldehyde through its abundant pores, it can decompose formaldehyde using highly active organic small molecules, effectively adsorb and efficiently purify. The chemical reaction of removing formaldehyde is irreversible and has no secondary pollution.
[0051] According to another aspect of the present invention, the present invention also relates to the use of the above-mentioned activated carbon adsorption material in formaldehyde purification.
[0052] The following is further explained in conjunction with specific embodiments and comparative examples.
[0053] Example 1
[0054] A method for preparing an activated carbon adsorption material comprises the following steps:
[0055] (1) Prepare inorganic salt solution: weigh 2 parts of potassium sulfate, 1 part of sodium carbonate, and 100 parts of deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0056] (2) Preparation of organic amine solution: weigh 2 parts of anionic polyacrylamide and 100 parts of deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0057] (3) Mixing: Mix the prepared inorganic salt solution and organic amine solution in a volume ratio of 1:1, mix them evenly, record the mass portion as 100 parts, then add 1 mass portion of hydrophobic agent dodecyltrimethoxysilane thereto, and stir evenly.
[0058] (4) Impregnation: Take 1 part by mass of coal-based activated carbon that has been dried at 150°C for 2 hours and place it in 3 parts by mass of the mixed solution prepared above. Use an ultrasonic instrument to oscillate the mixture, and then take it out and immerse it for 4 hours. During the impregnation process, stir it up and down with a glass rod for 3 minutes every 30 minutes. After the impregnation is completed, filter out the impregnation solution to leave the wet activated carbon.
[0059] (5) Drying: Spread the wet activated carbon evenly on the sieve and place it in a forced air drying oven with the temperature set in advance. Set the oven temperature to 90°C and dry it for 6 hours.
[0060] (6) Sealed storage: Allow the dried activated carbon to cool naturally to room temperature and store in a sealed bag.
[0061] Example 2
[0062] A method for preparing an activated carbon adsorption material comprises the following steps:
[0063] (1) Prepare inorganic salt solution: weigh 1 part potassium sulfate, 2 parts sodium carbonate, and 90 parts deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0064] (2) Preparation of organic amine solution: weigh 1 part of polyethyleneimine, 1 part of 3-amino-1-propanol, and 100 parts of deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0065] (3) Mixing: Mix the prepared inorganic salt solution and organic amine solution in a volume ratio of 1:1, mix them evenly, record the mass part as 100 parts, then add 0.5 mass part of silane coupling agent thereto, and stir evenly.
[0066] (4) Impregnation: 1 part by weight of coal-based activated carbon and 1 part by weight of coconut shell activated carbon dried at 150° C. for 2 hours were placed in 5 parts by weight of the mixed solution prepared above, and the mixture was vibrated using an ultrasonic instrument, and then taken out and impregnated for 4 hours. During the impregnation process, the mixture was stirred up and down with a glass rod for 3 minutes every 30 minutes. After the impregnation was completed, the impregnation solution was filtered out to leave the wet activated carbon;
[0067] (5) Drying: Spread the wet activated carbon evenly on the sieve and place it in a pre-set temperature forced air drying oven at 100 °C for 6 h.
[0068] (6) Sealed storage: Allow the dried activated carbon to cool naturally to room temperature and store in a sealed bag.
[0069] Example 3
[0070] A method for preparing an activated carbon adsorption material, which differs from Example 2 in that:
[0071] In step (1), 3 parts of potassium sulfate and 4 parts of sodium carbonate.
[0072] In step (2), 2 parts of polyethyleneimine and 2 parts of 3-amino-1-propanol.
[0073] In step (3), 1 part of silane coupling agent.
[0074] Example 4
[0075] A method for preparing an activated carbon adsorption material, which differs from Example 2 in that:
[0076] In step (4), the coal-based activated carbon is 2 parts, the coconut shell activated carbon is 1 part, and the mixed solution is 8 parts.
[0077] Example 5
[0078] A method for preparing an activated carbon adsorption material comprises the following steps:
[0079] (1) Prepare an inorganic salt solution: weigh 1.5 parts of potassium bicarbonate, 2 parts of sodium bisulfate, and 90 parts of deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0080] (2) Preparation of organic amine solution: Weigh 1 part of polyethyleneimine, 1 part of 3-amino-1-propanol, 1 part of 2,6-diaminohexanoic acid, and 100 parts of deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0081] (3) Mixing: Mix the prepared inorganic salt solution and organic amine solution in a volume ratio of 1:0.7, mix them evenly, record the mass parts as 100 parts, then add 0.3 mass parts of hexadecyltrimethoxysilane thereto, and stir evenly.
[0082] (4) Impregnation: 1 part by weight of coal-based activated carbon, 1 part by weight of coconut shell activated carbon, and 1 part by weight of wood activated carbon, which have been dried at 150° C. for 2 hours, are placed in 8 parts by weight of the mixed solution prepared above, and the mixture is vibrated using an ultrasonic instrument, and then taken out and impregnated for 6 hours. During the impregnation process, the mixture is stirred up and down with a glass rod for 3 minutes every 30 minutes. After the impregnation is completed, the impregnation solution is filtered out to leave the wet activated carbon;
[0083] (5) Drying: Spread the wet activated carbon evenly on the sieve and place it in a pre-set temperature forced air drying oven at 120°C for 4 hours;
[0084] (6) Sealed storage: Allow the dried activated carbon to cool naturally to room temperature and store in a sealed bag.
[0085] Example 6
[0086] A method for preparing an activated carbon adsorption material comprises the following steps:
[0087] (1) Prepare inorganic salt solution: weigh 1 part sodium carbonate and 90 parts deionized water by mass, and ultrasonicate for 10 minutes to promote complete dissolution.
[0088] (2) Preparation of organic amine solution: weigh 1 part of 3-amino-1-propanol and 100 parts of deionized water by mass, and perform ultrasonic treatment for 10 minutes to promote complete dissolution.
[0089] (3) Mixing: The prepared inorganic salt solution and organic amine solution are mixed in a volume ratio of 1:0.5, mixed evenly, and the mass fraction is 100 parts. Then, 0.5 mass parts of vinyl triethoxysilane are added thereto and stirred evenly.
[0090] (4) Impregnation: Take 2 parts of coal-based activated carbon dried at 150°C for 2 hours and place them in 5 parts of the mixed solution prepared above, vibrate the mixture with an ultrasonic instrument, and then take it out and immerse it for 8 hours. During the impregnation process, stir it up and down with a glass rod for 3 minutes every 30 minutes. After the impregnation is completed, filter out the impregnation solution to leave the wet activated carbon;
[0091] (5) Drying: Spread the wet activated carbon evenly on the sieve and place it in a pre-set temperature forced air drying oven at 150°C for 2 hours;
[0092] (6) Sealed storage: Allow the dried activated carbon to cool naturally to room temperature and store in a sealed bag.
[0093] Comparative Example 1
[0094] A method for preparing an activated carbon adsorption material, which differs from Example 1 in that:
[0095] The anionic polyacrylamide in step (2) is replaced by nonionic polyacrylamide.
[0096] Comparative Example 2
[0097] A method for preparing an activated carbon adsorption material, which differs from Example 2 in that:
[0098] In step (2), 1 part of polyethyleneimine and 1 part of 3-amino-1-propanol are replaced with 1 part of 2,6-diaminohexanoic acid.
[0099] Comparative Example 3
[0100] Coal-based activated carbon raw materials.
[0101] Experimental example
[0102] The activated carbon provided in each embodiment and comparative example was prepared into a filter element and installed in an air purifier, and the formaldehyde removal rate in 30 minutes and 1 hour was used as the main observation index. The size of the filter element was 1.4m×1.4m×1.5m and the volume was 3m 3 Purification chamber test, the detection method is in accordance with GB / T 18801-2022 Air Purifier, where the initial formaldehyde concentration standard is 1.00±0.20mg / m 3 The determination method is phenol reagent spectrophotometry.
[0103] The test results are shown in Table 1.
[0104] Table 1 Test results
[0105]
[0106]
[0107] As can be seen from Table 1, the activated carbon adsorption materials obtained by the methods of the embodiments of the present invention have a great purification effect on formaldehyde, especially the embodiment 2 has an outstanding effect, with a formaldehyde removal rate of more than 90% in 30 minutes and a formaldehyde removal rate of more than 99% in 1 hour.
[0108] The adsorption performance of the activated carbon materials in Comparative Examples 1 to 3 is relatively poor, and the adsorption rate of formaldehyde is significantly lower than that of the embodiments of the present invention.
[0109] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an activated carbon adsorption material, characterized in that: The following steps are involved: Mixing an inorganic salt solution, an organic amine solution and a hydrophobic agent to obtain a composite modified solution; The activated carbon raw material is mixed with the composite modified liquid, the solid and liquid are separated, and the solid is collected and dried.
2. The method for preparing an activated carbon adsorption material according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The mass fraction of the inorganic salt solution is 0.1% to 20%; (2) In the inorganic salt solution, the inorganic salt comprises at least one of potassium chloride, sodium chloride, potassium sulfate, sodium bisulfate, sodium carbonate and potassium bicarbonate.
3. The method for preparing an activated carbon adsorption material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The mass fraction of the organic amine solution is 0.05% to 5%; (2) the organic amine includes at least one of polyethyleneimine, 3-amino-1-propanol, 2,6-diaminocaproic acid, anionic polyacrylamide, cationic polyacrylamide and nonionic polyacrylamide; (3) The volume ratio of the inorganic salt solution to the organic amine solution is 1:(0.2-1).
4. The method for preparing an activated carbon adsorption material according to claim 1, characterized in that: Contains at least one of the following features (1) to (3): (1) The hydrophobic agent includes at least one of methyl vinyl silicone resin, vinyl triethoxysilane, dodecyl trimethoxysilane, hexadecyl trimethoxysilane and a silane coupling agent; (2) The mass fraction of the hydrophobic agent in the composite modified liquid is 0.1% to 2%; (3) The inorganic salt solution, the organic amine solution and the hydrophobic agent are mixed, specifically comprising: dropping the hydrophobic agent into a mixture of the inorganic salt solution and the organic amine solution.
5. The method for preparing an activated carbon adsorption material according to claim 1, characterized in that: Contains at least one of the following features (1) to (2): (1) The mass ratio of the activated carbon raw material to the composite modified liquid is 1:(2-6); (2) The activated carbon raw material includes at least one of coal-based activated carbon, coconut shell activated carbon and wood-based activated carbon.
6. The method for preparing an activated carbon adsorption material according to claim 1, characterized in that: The mixing treatment includes ultrasonic treatment and immersion treatment.
7. The method for preparing an activated carbon adsorption material according to claim 6, characterized in that: Contains at least one of the following features (1) to (2): (1) The ultrasonic treatment time is 2 to 15 minutes; (2) The immersion treatment time is 1 to 8 hours, and stirring is performed for 2 to 4 hours every 20 to 30 minutes.
8. The method for preparing an activated carbon adsorption material according to claim 1, characterized in that: The drying temperature is 90 to 150° C., and the drying time is 2 to 12 hours.
9. An activated carbon adsorption material, characterized in that: The activated carbon adsorption material is prepared by the method for preparing the activated carbon adsorption material according to any one of claims 1 to 8.
10. Use of the activated carbon adsorption material according to claim 9 in formaldehyde purification.